2009
DOI: 10.1007/s00024-009-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Microseismicity Resulting from Gel and Water Fracturing of Tight Gas Reservoirs

Abstract: We provide a comparative analysis of the spatiotemporal dynamics of hydraulic fracturing-induced microseismicity resulting from gel and water treatments. We show that the growth of a hydraulic fracture and its corresponding microseismic event cloud can be described by a model which combines geometry-and diffusion-controlled processes. It allows estimation of important parameters of fracture and reservoir from microseismic data, and contributes to a better understanding of related physical processes. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In actual reservoirs, Baria and Green [] in geothermal field and Warpinski et al [] and Dinske et al [] in tight gas reservoirs made comparative analyses of microseismicity induced by HF using viscous fluid and water. Baria and Green [] and Dinske et al [] could not show clear difference between the two fluids, while Warpinski et al [] showed that slickwater fracturing extends a much larger area further in three dimensions than gel fracturing, which is consistent with the findings from our laboratory experiments. In actual field operations of HF, weak planes, such as preexisting cracks, sedimentary planes and defects in strata, may behave in a similar manner to grain boundary in the granite specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In actual reservoirs, Baria and Green [] in geothermal field and Warpinski et al [] and Dinske et al [] in tight gas reservoirs made comparative analyses of microseismicity induced by HF using viscous fluid and water. Baria and Green [] and Dinske et al [] could not show clear difference between the two fluids, while Warpinski et al [] showed that slickwater fracturing extends a much larger area further in three dimensions than gel fracturing, which is consistent with the findings from our laboratory experiments. In actual field operations of HF, weak planes, such as preexisting cracks, sedimentary planes and defects in strata, may behave in a similar manner to grain boundary in the granite specimens.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure such an activity during days to months, a driving mechanism is required. It could be pressure diffusion, as such swarms are induced by reservoir (injection and impoundment) activities (Deichmann & Giardini, 2009; Diehl et al., 2017; Dinske et al., 2010; Ellsworth, 2013; Lengliné et al., 2017). The similarity between induced and natural swarms suggests that even natural swarms are driven by transient episodes of fluid flow at depth.…”
Section: Introductionmentioning
confidence: 99%
“…The state of affairs has changed with the development of a technique for estimating the in situ formation permeability from microseismic data ͑Shapiro et al, 2006;Dinske et al, 2009;. This technique, called the r ‫מ‬ t method, derives the permeability from the rate of growth of a microseismic cloud by measuring the changes in distances r between the recorded microseismic events and a fluid injector with time t. Here, we apply the r ‫מ‬ t method to data acquired during hydraulic treatments of nine stages in wells Vible 1-11D and 8-11D, and of eleven stages in wells Warbonnet 7-5D and 8-5D, owned and operated by Shell in the tightgas Pinedale Field, Wyoming, U.S.A. We also introduce and test an alternative technique that estimates the same formation permeability by inverting the diffusion equation.…”
Section: Introductionmentioning
confidence: 99%